Ultrasonographic evaluation of gastric contents in term pregnant women fasted for six hours. (May 2018) - Hakak, S.; McCaul, C.L.; Crowley, L.
Highlights: Ultrasonographic assessment of gastric contents was performed. Assessments were made after a six hour fast at term gestation. Gastric volumes >1.5 mL/kg were measured in 37% of pregnant women. High gastric volumes were seen in 36% of participants with a grade 1 antrum. Abstract: Background: Current fasting guidelines suggest six hours are adequate to minimise the aspiration risk after a light meal consumed by pregnant women undergoing elective caesarean section. We assessed gastric contents in non-labouring pregnant women, using ultrasonographic analysis. Methods: In a prospective study, pregnant women ≥36 weeks' gestation, without conditions likely to influence gastric emptying, underwent ultrasonographic analysis of their gastric antrum, after six hours of fasting following a standardised light meal. The primary outcome was solid food content in the antrum. Other outcomes included fluid in the supine and right lateral positions, antral cross-sectional area and estimated residual gastric fluid volume. Antral grades were classified: grade 0 = absence of fluid in both supine and right lateral positions: grade 1 = fluid present in the right lateral position only: grade 2 = fluid in both positions. Results: Complete data were available in 46/51 (90%) women. No woman had solid food visible. Antral grades 0, 1 and 2 were seen in 6 (13%), 36 (78%) and 4 (9%) women respectively. Eighteen of 48 women (37.5%) had a residual volume greater than 1.5 mL/kg. Of those with a grade 1 antrum, 13/36 (36%) had residual volumes in excess of 1.5 mL/kg. For grade 2, this was 4/4 (100%). Conclusions: Our cohort of pregnant women fasted for six hours had no solid food visible in the antrum, but many had both qualitative and quantitative ultrasonographic evidence of gastric volumes potentially associated with aspiration risk. This suggests that pregnancy-specific fasting guidelines may be required.